Empathy Gap in Social Media Comments for Sexual Harassment Victim - Lubis, Khairunnisya; Nisa, Indah Chairun; Dalimunthe, Pidiatun Dinia; Perangin-angin, Alemina Br. (TALENTA Publisher, 2022)
Indonesian Twitter users who filed a complaint about sexual harassment were studied to see if there was an empathy gap among their tweet responses. The author uses a content analysis method and observes a sample of empathy gap experiences to notice and study empathy gap behaviour in Twitter toward sexual harassment victims. In the research that has been done, the comments tweet as amount 3733 tweets and chosen 60 of them randomly to know-how is the empathy gap with sexual harassment cases. It is concluded that bullies have aggressive and intimidating characteristics. On message production by the bully, actors are supposed to produce messages in expressive, conventional, and rhetorical ways, including negative empathy characteristics. So on the other hand, the research that has been done concludes that people who act as victims have passive and defensive elements. On message reception by the communicant (victim), the victim placed the position of receiving the message in a dominant, negotiating, and oppositional position.